2008
DOI: 10.1111/j.1365-2826.2008.01770.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile Cerebrospinal Fluid and Plasma Ghrelin in Relation to Growth Hormone Secretion and Food Intake in the Sheep

Abstract: et al.. Pulsatile cerebrospinal fluid and plasma ghrelin in relation to growth hormone secretion and food intake in the sheep.. Journal of Neuroendocrinology, Wiley, 2008, 20 (10), pp.1138-46. 10.1111/j.1365-2826.2008 Pulsatile CSF and plasma ghrelin in relation with GH secretion and food intake in the sheep.Grouselle Dominique, * Chaillou Elodie, *Caraty Alain, Bluet-Pajot Marie-Therese, Zizzari Philippe, *Tillet Yves, Epelbaum Jacques. Key words : plasma, CSF, pulsatile patterns. AddressesElodie Chaillou and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 27 publications
2
55
0
8
Order By: Relevance
“…injection (32). Although systemic administration of ghrelin has previously been shown to induce hypothalamic c-fos expression (17), the current studies demonstrate sensing of hormone by ARH neurons over timescales (5 vs. 30 min) that are more compatible with the acute orexigenic effects of ghrelin on food intake (15). In addition, the close proximity of ghrelin-labeled neurons to fenestrated capillaries projecting from the ME into the ARH supports an important functional role for this vascular route in rapid molecule entry into the metabolic brain.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…injection (32). Although systemic administration of ghrelin has previously been shown to induce hypothalamic c-fos expression (17), the current studies demonstrate sensing of hormone by ARH neurons over timescales (5 vs. 30 min) that are more compatible with the acute orexigenic effects of ghrelin on food intake (15). In addition, the close proximity of ghrelin-labeled neurons to fenestrated capillaries projecting from the ME into the ARH supports an important functional role for this vascular route in rapid molecule entry into the metabolic brain.…”
Section: Discussionmentioning
confidence: 55%
“…Ghrelin was chosen as a candidate hormone because its acute effects upon feeding behavior (15), together with a short circulating half-life, demand the presence of rapid and precise sensing mechanisms. Although ghrelin's orexigenic effects on hypothalamic feeding centers are well documented (16,17), it remains unclear how peripherally secreted hormone accesses this BBB-protected site, as a specialized transport system from the circulation to the brain is yet to be identified (18).…”
mentioning
confidence: 99%
“…Furthermore, as a seasonal animal, leptin secretion and sensitivity in the adult sheep is altered during the year, unlike in pigs or humans (Zieba et al, 2008). Finally, there are remaining questions regarding similarities with human in the role of ghrelin in the control of food intake in sheep (Sugino et al, 2004;Grouselle et al, 2008). Consequences of differences in digestive physiology overwhelmed the context of digestive behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Banks et al (7) demonstrated that human ghrelin is able to cross the blood-brain barrier in mice through a saturable transport mechanism. However, recent evidence suggests that, even if such a transport mechanism existed, it would be too slow, as it was shown that a time lapse of 40 -50 min was required after intravenous injection to increase cerebrospinal fluid ghrelin levels twofold (28). Other investigators have suggested that ghrelin may act at the circumventricular organs, where the blood-brain barrier is nonexistent and ghrelin receptors are expressed (63,95).…”
Section: Ghrelin-mediated Sympathoinhibition and Anti-inflammatory Efmentioning
confidence: 99%